A Study of Organizational Commitment with reference to Marital Status of Indian Nursing Staff - Tikare, Mrinali (American Journal of Trade and Policy, 2015)
“Health is Wealth”, health is considered as the most important phenomenon in today’s world which determines the wealth of the country at large. Nursing staff plays the major role in the healthcare industry and it is obligatory that their needs have to be taken care and a congenial atmosphere is created for them to work with utmost job satisfaction and content, the result of which would be a high-quality nursing care. The present study focuses on organizational commitment with reference to the marital status of the nursing professionals.The data have been collected from eight cities, comprising of four zones of India. The study uses a stratified sampling method in which 376 Nursing Staff from 32 hospitals has responded. This study uses the well-known instrument - ACN scale developed by Allen and Meyer (1997).The group of married nursing staff revealed a higher mean for all the variables of commitment. However, there are similarities between married and unmarried nursing staff at the level of affective commitment, continuance commitment, and total organizational commitment. Conversely, there is a significant difference in normative commitment level between married and unmarried nursing staff of India. The result of the study confirmed the findings of the earlier studies related the positive relationship between marital status & organizational commitment, and higher commitment level of married employees as well as unmarried employees. This study suggests that the HR Managers should understand the issues of married & unmarried nursing staff and develop HR Policies accordingly.JEL Classifications Code: L2
Keywords: Marital status; Nursing Staff; India; Organizational Commitment